The Effect of Annealing on the Structural and Optical Properties of Titanium Dioxide Films Deposited by Electron Beam Assisted PVD. (22nd May 2013) - Abdulraheem, Yaser M.; Ghoraishi, Sahar; Arockia-Thai, Lidia; Zachariah, Suji K.; Ghannam, Moustafa
Abstract : Titanium dioxide thin films were deposited on crystalline silicon substrates by electron beam physical vapor deposition. The deposition was performed under vacuum ranging from 10 −5 to 10 −6 Torr without process gases, resulting in homogeneous TiO 2 - x layers with a thickness of around 100 nm. Samples were then annealed at high temperatures ranging from 500 ° C to 800 ° C for 4 hours under nitrogen, and their structural and optical properties along with their chemical structure were characterized before and after annealing. The chemical and structural characterization revealed a substoichiometric TiO 2 - x film with oxygen vacancies, voids, and an interface oxide layer. It was found from X-ray diffraction that the deposited films were amorphous and crystallization to anatase phase occurred for annealed samples and was more pronounced for annealing temperatures above 700 ° C. The refractive index obtained through spectroscopic ellipsometry ranged between 2.09 and 2.37 in the wavelength range, 900 nm to 400 nm for the as-deposited sample, and jumped to the range between 2.23 and 2.65 for samples annealed at 800 ° C. The minimum surface reflectance changed from around 0.6% for the as-deposited samples to 2.5% for the samples annealed at 800 ° C.